Assessment of the Work of Authorities in the Field of Social Security of Citizens Discharged from Military Service and their Family Members - BONDALETOV, Valery Viktorovich; BONDALETOVA, Natalia Fedorovna; DEMCHENKO, Tatyana Sergeevna; EVSTRATOVA, Tatyana Anatolevna; MEDVEDEVA, Natalia Vladimirovna (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The article presents the assessment of the work of federal and municipal authorities in the field of social security of citizens discharged from military service and their family members. The analysis demonstrates that in general, the current legislation ensures a stable socioeconomic status and social security of this category of citizens. However, the measures of state support in the field of social security of citizens discharged from military service and the members of their families deployed by the regional authorities leave much to be desired. Medical support, employment, and education present the most problematic areas. The results of the study indicate that one of the reasons for low security is the level of awareness of former military personnel and their family members.RESUMEN El artículo presenta la evaluación del trabajo de las autoridades federales y municipales en el campo de la seguridad social de los ciudadanos dados de baja del servicio militar y sus familiares. El análisis demuestra que, en general, la legislación actual garantiza un estado socioeconómico estable y la seguridad social de esta categoría de ciudadanos. Sin embargo, las medidas de apoyo estatal en el campo de la seguridad social de los ciudadanos dados de baja del servicio militar y los miembros de sus familias desplegados por las autoridades regionales dejan mucho que desear. El apoyo médico, el empleo y la educación presentan las áreas más problemáticas. Los resultados del estudio indican que una de las razones de la baja seguridad es el nivel de conciencia del antiguo personal militar y sus familiares.